The Impact of Human Resource Management Practices on Employee Performance among manufacturing employees in Malaysia - Omar Hamdan Mohammad Alkharabsheh; Sozon Sozon; Dennis Kueh Yeu Herng (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The effective and efficient use of human resources could paly vital roles in success and productivity in the organization. Based on the 4th Industrial Revolution and the Diversity of Employees, it is mandated that Human Resource Management (HRM) practices be adopted for hiring and retaining employees. In this study, the main objective is to determine the relationship between training and development, performance appraisal, leadership styles and reward system, and their effect on the performance of employees in manufacturing sector. The study adopted a quantitative approach and data gathered from manufacturing employees in Malaysia. The current study showed a positive effect of HRM practices on enhanced employee performance amoung manufacturing employees. The fidings of this study may help to manage the diversity in the workplace and promote HRM pracices for organizational success and establish win-win employees and employers relationship.